2012
DOI: 10.1007/s10745-012-9480-9
|View full text |Cite
|
Sign up to set email alerts
|

The Prospects for Payment for Ecosystem Services (PES) in Vietnam: A Look at Three Payment Schemes

Abstract: Global conservation discourses and practices increasingly rely on market-based solutions to fulfill the dual objective of forest conservation and economic development. Although varied, these interventions are premised on the assumption that natural resources are most effectively managed and preserved while benefiting livelihoods if the market-incentives of a liberalised economy are correctly in place. By examining three nationally supported payment for ecosystem service (PES) schemes in Vietnam we show how ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(67 citation statements)
references
References 36 publications
1
64
0
2
Order By: Relevance
“…Wunder (2013) suggests this is common among current PES schemes. McElwee (2012) and To et al (2012) both found that because of state intervention, other PES schemes in Vietnam are not underpinned by market mechanisms either, although they have come closer than the two examples examined in this report. The two examples in this report could be considered more community-based and employment-based, in that communities or individuals are paid to actively engage in protecting and managing land, rather than for merely owning and maintaining land that provides environmental services.…”
Section: The Market Pes Theory and Program Designmentioning
confidence: 68%
See 1 more Smart Citation
“…Wunder (2013) suggests this is common among current PES schemes. McElwee (2012) and To et al (2012) both found that because of state intervention, other PES schemes in Vietnam are not underpinned by market mechanisms either, although they have come closer than the two examples examined in this report. The two examples in this report could be considered more community-based and employment-based, in that communities or individuals are paid to actively engage in protecting and managing land, rather than for merely owning and maintaining land that provides environmental services.…”
Section: The Market Pes Theory and Program Designmentioning
confidence: 68%
“…The precise role of the government in the PES scheme in the study village was unclear. However, other studies have found that the role of the state in environmental management is often more limiting than empowering (KimDung et al 2013;To et al 2012). This suggests that outside organisations can impinge on the ability of PES programs to deliver socioeconomic benefits to communities, even if they are the driving force behind the programs.…”
Section: Communities Receiving Non-monetary Benefits From the Protectmentioning
confidence: 98%
“…A quantitative study of Sheng et al [48] shows that depending on the government objective in REDD+ implementation, such as social equity, environmental priority or poverty alleviation, different incentive and tax structures need to be implemented depending on the respective objective. However, there is a general consensus that the negative impacts of REDD+ on livelihoods should be minimized, its benefits are equitably shared, and there is an adequate participation of local communities in the implementation of REDD+ [47,49].…”
Section: Redd+ and Poverty Alleviationmentioning
confidence: 99%
“…Effectiveness of REDD+ depends on the ability and interest of local communities to sustainably manage their forests and enhance carbon stocks [55]. A study of To et al [49] on PES, tenure, and poverty reduction in Vietnam reveals that households with unclear tenure, being often the poorest in their respective communities, have been excluded altogether from the benefits of PES schemes. In this case, the PES schemes actually impacted the poorest households negatively, and exacerbated income inequality.…”
Section: Forestland and Carbon Tenure And Rightsmentioning
confidence: 99%
See 1 more Smart Citation